LANGKAH PENATAAN KELEMBAGAAN UNTUK MENCAPAI REFORMASI REGULASI DI INDONESIA MELALUI PEMBUBARAN LEMBAGA NEGARA NONSTRUKTURAL - Thohari, Ahmad Ahsin (Jurnal Yuridis, 2023)
The President has taken a policy to dissolve state institutions, most recently through Presidential Regulation Number 112 of 2020, which dissolved 10 non-structural state institutions. This is suspected as a decisive step to create effectiveness in the legal system within the state institutions. Factually, there are currently too many regulations being created by state institutions, causing an overlap of duties and authorities, and inefficiency due to self-entanglement, making each state institution difficult to operate. Therefore, there is a need for a reduction in state institutions to achieve regulatory reform that is results-oriented, not just procedural. This is based on the goal of legal development, which is not only inherent in substance but also in legal structure and culture. The purpose of this research is to understand, examine, and analyze the President's considerations for the dissolution of non-structural state institutions and to analyze the implications of the dissolution of non-structural state institutions on the formation of regulations and legal order in Indonesia. This research method uses normative legal research with a legislative approach and a conceptual approach referring to literature studies. The conclusion of dissolving non-structural state institutions is aimed at improving bureaucratic performance by minimizing overlapping duties and functions that result in the waste of authority and budget inefficiency. Additionally, there is a need for further regulation at the legislative level regarding non-structural institutions to establish fixed procedures from formation to dissolution, similar to the concept of regulating state ministries in Law No. 39 of 2008 concerning State Ministries.